Activation of future teachers’ cognitive activities in the process of learning foreign languages - Гладка, О. В. (Pedagogy of Higher and Secondary Education, 2013)
Hladka O. V. Activation of future teachers’ cognitive activities in the process of learning foreign languages. In the article the necessity of activation of future teachers’ cognitive activities in the process of learning foreign languages is proved. The most effective modern methods favoring the successful solution of the given task are suggested.